Teleneuropsychology: Evidence for Video Teleconference-Based Neuropsychological Assessment. (24th October 2014) - Munro Cullum, C.; Hynan, L.S.; Grosch, M.; Parikh, M.; Weiner, M.F.
Abstract The use of videoconference technology to deliver health care diagnostics and treatment continues to grow at a rapid pace. Telepsychiatry and telepsychology applications are well-accepted by patients and providers, and both diagnostic and treatment outcomes have generally been similar to traditional face-to-face interactions. Preliminary applications of videoconference-based neuropsychological assessment (teleneuropsychology) have yielded promising results in the feasibility and reliability of several standard tests, although large-scale studies are lacking. This investigation was conducted to determine the reliability of video teleconference (VTC) - based neuropsychological assessment using a brief battery of standard neuropsychological tests commonly used in the evaluation of known or suspected dementia. Tests included the Mini-Mental State Examination (MMSE), Hopkins Verbal Learning Test-Revised, Digit Span forward and backward, short form Boston Naming Test, Letter and Category Fluency, and Clock Drawing. Tests were administered via VTC and in-person to subjects, counterbalanced using alternate test forms and standard instructions. Two hundred two adult subjects were tested in both rural and urban settings, including 83 with cognitive impairment and 119 healthy controls. We found highly similar results across VTC and in-person conditions, with significant intraclass correlations (mean=.74; range: 0.55–0.91) between test scores. Findings remained consistent in subjects with or without cognitive impairment and in persons with MMSE scores as low as 15. VTC-based neuropsychological testing is a valid and reliable alternative to traditional face-to-face assessment using selected measures. More VTC-based studies using additional tests in different populations are needed to fully explore the utility of this new testing medium. (JINS, 2014, 20, 1–6)